Peculiarities of using the low temperature tank for long-term storage of biological material in liquid nitrogen vapours - Chizhevsky, V. V.; Groshevoj, M. I.; Prokopyuk, O. S. (Problems of Cryobiology and Cryomedicine, 2007)
There was studied the possibility of vapour cryogenic tank use for biological material long-term storage under low temperature bank conditions at the Institute for Problems of Cryobiology and Cryomedicine of the National Academy of Sciences of Ukraine. Methodical approaches for bioobject integral storage when performing technological operations in liquid nitrogen vapours have been elaborated.